2021
DOI: 10.1128/spectrum.00176-21
|View full text |Cite
|
Sign up to set email alerts
|

Honeybee Exposure to Veterinary Drugs: How Is the Gut Microbiota Affected?

Abstract: This study investigates the impact of the three most widely used antibiotics in the beekeeping sector (oxytetracycline, tylosin, and sulfonamides) on the honeybee gut microbiota and on the spread of antibiotic resistance genes. The research represents an advance to the present literature, considering that the tylosin and sulfonamides effects on the gut microbiota have never been studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 77 publications
0
13
1
Order By: Relevance
“…Consistent with the direct action of antibiotics on bacteria, we observed substantial changes in the honey bee gut community after tetracycline exposure. While in previous studies, antibiotics were shown to affect the honey bee microbiome ( Powell et al, 2021 ; Tian et al, 2012 ; Moullan et al, 2015 ; Li et al, 2017 ; Raymann et al, 2017 ; Baffoni et al, 2021 ; Jia et al, 2022 ), it rarely led to the total collapse of bacterial species as we observed in our design. At the end of the first cycle, four bacterial genera disappeared from guts of antibiotic-fed bees ( Figure 5 and Supplementary Figure S9 ).…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…Consistent with the direct action of antibiotics on bacteria, we observed substantial changes in the honey bee gut community after tetracycline exposure. While in previous studies, antibiotics were shown to affect the honey bee microbiome ( Powell et al, 2021 ; Tian et al, 2012 ; Moullan et al, 2015 ; Li et al, 2017 ; Raymann et al, 2017 ; Baffoni et al, 2021 ; Jia et al, 2022 ), it rarely led to the total collapse of bacterial species as we observed in our design. At the end of the first cycle, four bacterial genera disappeared from guts of antibiotic-fed bees ( Figure 5 and Supplementary Figure S9 ).…”
Section: Discussioncontrasting
confidence: 44%
“…In addition, honey bees are important pollinators and are exposed to diverse chemicals in the agricultural landscape as well as by beekeepers. It could be shown that antibiotics have strong effects on the honey bee microbiome ( Powell et al, 2021 ; Tian et al, 2012 ; Moullan et al, 2015 ; Li et al, 2017 ; Raymann et al, 2017 ; Baffoni et al, 2021 ; Jia et al, 2022 ) and that such dysbiosis can even be experimentally transferred between workers ( Jia et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Statistical analysis for qPCR and NGS data (α-diversity and taxon analysis) was performed with the R software according to Baffoni et al 10 . β-diversity index was based on the QIIME statistical elaboration reports.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, a total of 60 samples were analysed via NGS in this work. The V3-V4 regions of 16S rRNA gene were amplified with primers Pro341F and Pro805R (Takahashi et al [41]), barcoded and sequenced on the MiSeq Illumina platform 2x300 bp V3 chemistry according to the protocol of Baffoni et al [24]. Raw reads were analysed with Qiime II [42], chimera checked with Userach61 [43], and obtained representative OTUs blasted against SILVA database v132 [44] and the new Apoidea-specific database.…”
Section: S Rrna Based Next Generation Sequencing and Bioinformatics A...mentioning
confidence: 99%